Nigerian coal corporation - Nigerian coal corporation; Nigeria (Lagos : Govt. Printer, 1957)
This book contains administrative and supply chain about the Nigerian coal corporation for the period 1957. Furthermore, it includes illustration and production quantity within the period under review.
included appendixes
asm; 21/01/19
Loans
Keywords: Mineral and Energy